2004
DOI: 10.1188/04.onf.633-639
|View full text |Cite
|
Sign up to set email alerts
|

Triggers of Uncertainty About Recurrence and Long-Term Treatment Side Effects in Older African American and Caucasian Breast Cancer Survivors

Abstract: Nurses can help cancer survivors to identify, monitor, and manage illness uncertainty and emotional distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 41 publications
5
87
0
2
Order By: Relevance
“…In addition, age was negatively related to the level of income for First, we found that psychological well-being was directly associated with PQOL across all ethnic groups. Our finding is consistent with other studies [34,[80][81][82][83]. For some survivors, psychological distress including depression, anxiety, or fear can manifest into chronic and persistent stressors [84,85]; such that experiencing psychological distress may deteriorate physical functioning and overall HRQOL.…”
Section: Demographic Informationsupporting
confidence: 94%
“…In addition, age was negatively related to the level of income for First, we found that psychological well-being was directly associated with PQOL across all ethnic groups. Our finding is consistent with other studies [34,[80][81][82][83]. For some survivors, psychological distress including depression, anxiety, or fear can manifest into chronic and persistent stressors [84,85]; such that experiencing psychological distress may deteriorate physical functioning and overall HRQOL.…”
Section: Demographic Informationsupporting
confidence: 94%
“…The most prevalent unmet need, manage concerns about the cancer coming back was endorsed by one third of survivors. Fear of recurrence has been frequently identified in both qualitative and quantitative studies [17,18,44,58] and while this fear was found to diminish over the first 12 months [34], our findings indicate that significant numbers of survivors report persistent fears of recurrence up to 10 years post diagnosis.…”
Section: Discussionsupporting
confidence: 49%
“…Fear of breast cancer recurrence can be amplifi ed or reactivated by several triggers, such as follow-up medical visits, the experience of physical symptoms such as new or persistent pain or fatigue, and cancer diagnosis or death of a public fi gure, friend, or family member (Gil et al 2004 ). Heightened fear of recurrence is reported by adult survivors of younger age, lower educational level, fewer signifi cant others, and Hispanic or non-Hispanic white race/ethnicity ( Crist and Grunfeld 2013 ;Phillips et al 2013 ).…”
Section: Anxiety and Fear Of Breast Cancer Recurrencementioning
confidence: 99%